Recycling of municipal solid waste incineration fly ash in foam ceramic materials for exterior building walls. (December 2021) - Fan, Yibo; Li, Shujing; Li, Yuanbing; Liang, Huqing; Tang, Mengxiong; Huang, Keke; Zhu, Lin
Abstract: In this study, municipal solid waste incineration fly ash (MSWI FA) and waste glass were used as the main raw materials to prepare foam ceramics, which have good application prospects as exterior building insulation materials. The effects of different ratios of MSWI FA to waste glass and firing temperature on the physical properties, microscopic structure, and heavy metal leaching properties of foam ceramics were studied. The results showed that when the MSWI FA content was 30 wt%, the apparent porosity of the samples fired at 1090 °C was 70.3%, the compressive strength was 7.94 MPa, the bulk density was 0.79 g/cm 3, and the thermal conductivity at room temperature was 0.071 W/(m·K). The mean pore size of the samples was 31.77 μm. In addition, the results of heavy metal leaching showed that the foam ceramics were compliant with industry standards. Therefore, the preparation of foam ceramics from MSWI FA and waste glass is a promising method to realise efficient recycling as well as reduce product costs. Highlights: A new method of recycling fly ash in building materials. Effect of MSWI FA content on the properties of foam ceramics was studied. The thermal insulation performance of the foamed ceramics prepared is excellent. Heavy metals are well solidified in the glass phase.